Prosecuting and Punishing South Africans Who Participate in Foreign Armed Conflicts - Jamil Ddamulira Mujuzi (Annales de la Faculté de Droit d’Istanbul)
Media reports suggested that some South Africans were serving in the Israel Defence Forces in the war between Israel and Hamas in late 2023. The South African government threatened to prosecute them for their participation in the conflict. Section 198(b) of the South African Constitution provides that one of the principles governing national security in South Africa is that “[t]he resolve to live in peace and harmony precludes any South African citizen from participating in armed conflict, nationally or internationally, except as provided for in terms of the Constitution or national legislation.” The Regulation of Foreign Military Assistance Act (1998) provides for the circumstances in which a South African citizen or permanent resident can, with authorisation, take part in an armed conflict in a foreign country. Failure to get authorisation or to comply with the condition(s) of the authorisation is an offence. The Prohibition of Mercenary Activities and Regulation of Certain Activities in Country of Armed Conflict Act, which is meant to repeal the Regulation of Foreign Military Assistance Act, is not yet in force. In this article, the author illustrates how South African citizens or permanent residents who participate in foreign armed conflicts can be prosecuted and punished.